WEATHERING STAGE CONTROL OF TUFF AND ITS INFLUENCE TO THE MALINO–MANIPI LANDSLIDE SUSCEPTIBILITY, SOUTH SULAWESI INDONESIA - Busthan Busthan; A.M. Imran; L. Samang; M. Ramli (Geological Engineering Department Universitas Gadjah Mada, 2015)
In 2013 there has been 34 incidents of landslides which cut the roads linking between Gowa and Sinjai off. The purpose of this study was to determine the effect on the stage of weathering of landslide in the study area. Methods used in this study are field survey, petrographic analysis, XRD analysis and shear strength testing of rock. Field survey results indicates that the area is dominated by tuffs that are partly volcanic breccia and lava. Petrographic analysis, showing the dominant composition of tuff with volcanic glass, bitownite, pyroxene and opaque minerals, and XRD analysis results indicate weathering tuffs that have experienced high and completely weathered contain smectite and halloysite clay types, and insitu shear strength test results indicate a strong shift to the lower tuff with high stage of weathering. Keywords: Susceptability to landslides, the stage of weathering, halloysite and smectite, shear strength, roads of Malino–Manipi